Cell-delivered magnetic nanoparticles caused hyperthermia-mediated increased survival in a murine pancreatic cancer model - Basel, Matthew T.; Balivada, Sivasai; Wang, Hongwang; Shrestha, Tej Bahadur; Seo, Gwi Moon; Pyle, Marla; Abayaweera, Gayani; Dani, Raj; Koper, Olga B.; Tamura, Masaaki; Chikan, Viktor; Bossmann, Stefan H.; et al. (My University, 2012)
Using magnetic nanoparticles to absorb alternating magnetic field energy as a method of generating localized hyperthermia has been shown to be a potential cancer treatment. This report demonstrates a system that uses tumor homing cells to actively carry iron/iron oxide nanoparticles into tumor tissue for alternating magnetic field treatment. Paramagnetic iron/iron oxide nanoparticles were synthesized and loaded into RAW264.7 cells (mouse monocyte/macrophage-like cells), which have been shown to be tumor homing cells. A murine model of disseminated peritoneal pancreatic cancer was then generated by intraperitoneal injection of Pan02 cells. After tumor development, monocyte/macrophage-like cells loaded with iron/iron oxide nanoparticles were injected intraperitoneally and allowed to migrate into the tumor. Three days after injection, mice were exposed to an alternating magnetic field for 20 minutes to cause the cell-delivered nanoparticles to generate heat. This treatment regimen was repeated three times. A survival study demonstrated that this system can significantly increase survival in a murine pancreatic cancer model, with an average post-tumor insertion life expectancy increase of 31%. This system has the potential to become a useful method for specifically and actively delivering nanoparticles for local hyperthermia treatment of cancer.
Keywords: Cytotherapy; Pancreatic cancer; Disseminated peritoneal carcinomatosis; Targeted magnetic hyperthermia; Nanoparticles